HUMANITY IN CONTEXT OF PROFESSIONAL LIFE - Gluchman, Vasil (European Scientific Journal, ESJ, 2014)
Author understands humanity as all the forms of behaviour leading to the protection and maintenance, i.e. development of human life. On the basis of the differences in the objects of our behaviour and conduct, he distinguishes between humanity as a naturalbiological quality and a cultural (moral) quality. The moral value of the first kind of behaviour is determined by our biological or social relations to our close ones. In the second case, the moral value of our behaviour to strangers is a pure manifestation of our morality and culture.